1993
DOI: 10.1080/10862969309547801
|View full text |Cite
|
Sign up to set email alerts
|

A Psychogenetic Perspective on Children's Understanding about Letter Associations during Alphabet Book Readings

Abstract: This study examined two preschoolers' understandings about letter associations during repeated alphabet book read alouds with their parents from a Piagetian perspective. Data for the present investigation was excerpted from a larger study in which six preschoolers, ages 3 1/2 to 4 1/2, read seven picture storybooks and two alphabet books three times each in a multiple baseline design over approximately a 30-day period. Applying the principles of Piaget's clinical or inquiry method, a qualitative analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…These studies have shown that children rarely comment on or ask questions about the letters, words, or lines of print, leading to the conclusion that children do not seem to pay attention to the text while being read to (Phillips & McNaughton, 1990;Shapiro, Anderson, & Anderson, 1997;Yaden & McGee, 1984;Yaden, Smolkin, & MacGillivray, 1993). Rather, children's questions and comments concerning the books were more related to the illustrations than to the text.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…These studies have shown that children rarely comment on or ask questions about the letters, words, or lines of print, leading to the conclusion that children do not seem to pay attention to the text while being read to (Phillips & McNaughton, 1990;Shapiro, Anderson, & Anderson, 1997;Yaden & McGee, 1984;Yaden, Smolkin, & MacGillivray, 1993). Rather, children's questions and comments concerning the books were more related to the illustrations than to the text.…”
Section: Introductionmentioning
confidence: 90%
“…Rather, children's questions and comments concerning the books were more related to the illustrations than to the text. For example, Yaden, Smolkin, and Conlon (1989) as well as Yaden et al (1993) found that no more than 10% of the questions asked by children ages three to six during shared book reading concerned print conventions and forms. In addition it is the case that parents rarely comment on or draw attention to the print, although they can be trained to do so with resultant gains in children's print awareness (Justice & Ezell, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Their selection of stories to read encouraged family-child interactions through reading and follow up experiences. Studies (e.g., Morrow 1990;Saracho 1987;Yaden et al 1993) indicated that reading to children cultivate literacy for them in numerous modes. Reading the identical story to children several times helps children to gain an understanding of the purposes of print, of how print is used, and of the people's reading behaviors (Morrow 1990;Yaden et al 1993;Smith 1978).…”
Section: Reading To Childrenmentioning
confidence: 99%
“…It has been suggested that storybooks may be a good source for language development in terms of vocabulary and syntax, but this was not found to be the case regarding word recognition (Stahl, 2003). It has also been noted that neither parents nor teachers generally emphasize print while reading to children (Dickinson & Tabors, 1991), and that children, too, do not focus on print when looking at alphabet books (Yaden, Smolkin, & MacGillivray, 1993).…”
mentioning
confidence: 98%